HTLV-1, Immune Response and Autoimmunity - Quaresma, Juarez A S (Viruses, 2015)
Human T-lymphotropic virus type-1 (HTLV-1) infection is associated with adult T-cell leukemia/lymphoma (ATL). Tropical spastic paraparesis/HTLV-1-associated myelopathy (PET/HAM) is involved in the development of autoimmune diseases including Rheumatoid Arthritis (RA), Systemic Lupus Erythematosus (SLE), and Sjögren’s Syndrome (SS). The development of HTLV-1-driven autoimmunity is hypothesized to rely on molecular mimicry, because virus-like particles can trigger an inflammatory response. However, HTLV-1 modifies the behavior of CD4(+) T cells on infection and alters their cytokine production. A previous study showed that in patients infected with HTLV-1, the activity of regulatory CD4(+) T cells and their consequent expression of inflammatory and anti-inflammatory cytokines are altered. In this review, we discuss the mechanisms underlying changes in cytokine release leading to the loss of tolerance and development of autoimmunity.